Market-Led Institutional Innovations for Farmers’ Inclusive Growth and Livelihood Security - R.N. Padaria, N.V. Kumbhare, Sujit Sarkar; V. Lenin (Indian Journal of Extension Education, 2017)
The study aimed at analyzing some successful models of institutional arrangements in India, where-in linking to value chains and markets facilitated inclusive growth of farmers. The grain festival could enhance the income of farmers, while helped consumers by way of ensuring savings as well as quality produce at competitive rates. Linking the linseed growers’ association to value chain helped the member’s secure additional benefits of 10.30 per quintal of produce. Similarly, operations through SHGs and federations, helped landless tribal women adopt sericulture on leased land to ensure livelihood security. Membership of growers’ association (MAHAGRAPE) helped the grape growers securean additional profit of 3958 per hectare through adoption of proper production; harvesting and post-harvest management practices, and savings on transaction costs. Factor analysis revealed financial management, incentives and welfare measures for members, trust among the members, democratic style of leadership, transparency in dealings, and identity of the organization as the major facilitating factors for sustainability of farmers’ organizations. The suggestive measures for effective and sustainable functioning of farmers’ producer’s organizations and growth include access to land and capital for developing processing and ware house units, provision of seed money, easy access to credit, capacity building facilities, and tax exemption.